High Plains Sunflower Production Handbook - Schlegel, Alan J.; Lamond, Ray E.; Thompson, Curtis R.; Rogers, Danny H.; Jardine, Doug; Higgins,, Randall A.; Harner III, Joseph P. (My University, 1999)
This publication describes the agronomic production on sunflowers in the high plains.
MF2384_1999_01
Keywords: MF2384; Crops; MF